Numerical Study on Performance Characteristics of Draft Tube of Mixed Flow Hydraulic Turbine - Khare, Ruchi; Prasad, Vishnu (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Draft tube is an important component of the hydraulic reaction turbine and affects the overall performance of turbine to a large extent. The flow inside the draft tube is complex because of the whirling flow coming out of runner and its diffusion along the draft tube. The kinetic energy coming out of runner is recovered in draft tube and part of recovery meets the losses. In the present work, the computational fluid dynamics (CFD) has been used for flow simulation in complete mixed flow Francis turbine for performance analysis for energy recovery, losses and flow pattern in an elbow draft tube used in Francis turbine at different operating conditions. The overall performance of the turbine at some typical operating regimes is validated with the experimental results and found to be in close comparison. DOI: http://dx.doi.org/10.3126/hn.v10i0.7103 Hydro Nepal Vol.10 January 2012 48-52